Eight features of the lumbar vertebrae - A. Toyshanuly (Nomadic Civilization: Historical Research, 2022)
The Kazakhs and Mongolian-speaking nomadic peoples in the past had many unique and diverse types of games. Their national games were mostly associated with the economic activities of nomads, who were mainly engaged in cattle breeding. It is quite natural that the younger generation was well acquainted with the habits and anatomical structure of domestic animals, which, of course, influenced the specifics of children’s gaming entertainment. The aforementioned nomadic peoples had both outdoor games that developed strength and dexterity in children and adolescents, and intellectual games that contributed to the development of the mind and logic of young people. In the research literature, outdoor games have been subjected to scientific analysis to a greater extent, but, relatively speaking, the second group of games that develop the intellect of the younger generation has received much less attention. Among intellectual games, a special place is occupied by such a folk game, which has become traditional in the nomadic environment, as “eight features of the lumbar vertebrae”. This intellectual game was widely spread among the tribes of the Hun Empire. A comprehensive analysis of this game, carried out in the article, revealed its specific features, showed that this is not just a common children’s entertainment, but part of the cultural heritage of the Turkic-Mongolian peoples.